Acceptability of the MySmile Mobile Health Application Among Malaysian Adolescents: A Qualitative Study Using the Theoretical Framework of Acceptability - Muhammad Hamidie Saari; Jamaludin Marhazlinda; Unaizah Hanum Obaidellah; Nazirah Ab Mumin; Zamros Yuzadi Mohd Yusof (Springer Nature, 2026)
Indexed by WOS